Complex Eyelid Reconstruction: A Practical Guide for the Mohs Surgeon. Issue 9 (5th September 2022) - Blumenthal, Shoshana R.; Swick, Marki; Bayan, Claire-Audrey; Ramanathan, Diya; Maher, Ian
Abstract : BACKGROUND: A growing body of literature suggests that Mohs micrographic surgeons can safely and successfully perform complex eyelid reconstruction. Given that up to 10 percent of all skin cancers occur on the periorbital skin, it is imperative that Mohs surgeons understand form and function to properly assess the defect and select the appropriate reconstruction method for a variety of eyelid defects. OBJECTIVE: Our objective is to provide a thorough understanding of eyelid anatomy with an emphasis on form and function, provide a framework for defect analysis, and an algorithmic approach to defect analysis and appropriate selection of repair. METHODS AND MATERIALS: A review of the literature on eyelid reconstruction was performed with specific reference to defect analysis and appropriately choosing repairs that are applicable to Mohs micrographic surgeons. CONCLUSION: Mohs micrographic surgeons can safely and successfully perform complex eyelid repairs. An understanding of eyelid anatomy is the first step toward the best surgical outcome, and there are various methods for reconstructing eyelid defects. Defect size, location and analysis of the anterior lamella, posterior lamella, and the canthal regions helps to create an organized operative plan. Abstract : Supplemental Digital Content is Available in the Text.